Pengaruh strategi positioning terhadap keputusan pembelian pada keep Burger di Kota Jambi - Habibbullah Habibbullah; Erida Erida; Ade Titi Nifita (Jurnal Dinamika Manajemen, 2020)
The purpose of this study is to analyze 1) Explain the influence of positioning strategy variables which include product attributes, benefits, users, competitors, product categories, and prices have a simultaneous and partial influence on purchasing decisions, 2) Explain which positioning strategy variables have the most dominant influence on buying decision. In this study, 97 consumers live in Jambi City using the probability sampling method and the unknown population's formula. The research instrument used a questionnaire and was analyzed using linear regression. The results of this study indicate that it affects significantly. The dominant variable lies in the product attribute variable (X1) 6.076, and partially influential is the attribute variable, competitor, and price, which has a significant effect.